2018
DOI: 10.20945/2359-3997000000005
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between of ACE I/D and the MTHFR C677T polymorphisms in the pathophysiology of type 2 diabetes mellitus in a population of Brazilian obese patients

Abstract: Objectives This study aimed to evaluate the frequencies of the angiotensin converting enzyme (ACE) gene insertion/deletion (I/D) and methylenetetrahydrofolate reductase (MTHFR) gene C677T polymorphisms in obese patients with and without type 2 diabetes mellitus (T2DM). Subjects and methods These polymorphisms were analyzed by polymerase chain reaction in 125 patients with obesity, 47 (T2DM) and 78 (Control Group). Results No significant difference was found on comparing the T2DM and Control Groups in respect t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 23 publications
2
14
0
Order By: Relevance
“…The results are in agreement with the above literature. There are many association studies showing influence of ACE I/D polymorphism on the onset of diabetes mellitus (Al-Saikhan et al, 2017, Pirozzi et al, 2018, Mirfeizi et al, 2018, Aggarwal et al, 2016, Ohkuma et al,2019. However, recent findings do not support this statement.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The results are in agreement with the above literature. There are many association studies showing influence of ACE I/D polymorphism on the onset of diabetes mellitus (Al-Saikhan et al, 2017, Pirozzi et al, 2018, Mirfeizi et al, 2018, Aggarwal et al, 2016, Ohkuma et al,2019. However, recent findings do not support this statement.…”
Section: Resultsmentioning
confidence: 97%
“…However, the association of the I/D polymorphism of the ACE in sports abilities have been debated. ACE gene I/D polymorphism is also associated with the development of diabetes mellitus (basically type II DM), gestasional diabetes and various comorbidities in different world populations (Purnamasari et al, 2012;Pan et al, 2016;MirFeizi et al, 2018;Pirozzi et al, 2018;Shen et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In a study conducted in China in 2014, Wang et al found that C677T in the MTHFR may influence the risk of T2DM (Wang et al, ). Recently, in a case–control study conducted in the population of Brazilian with 47 T2DM cases and 78 controls by Flavio Fontes Pirozzi et al (Pirozzi et al, ), no correlation was found between the MTHFR C677T in the development of T2DM.…”
Section: Discussionmentioning
confidence: 99%
“…Pirozzi, et al evaluated the frequencies of the angiotensin converting enzyme (ACE) gene insertion/deletion (I/D) and MTHFR gene C677T polymorphisms in obese patients with and without type 2 DM [12]. These polymorphisms were analysis by polymerase chain reaction in 125 patients with obesity, 47 (DM) and 78 (Control Group On analyzing the DM Group, there were no significant differences in the presence of complications.…”
Section: Evidence-based Datamentioning
confidence: 99%